2021
DOI: 10.3390/ijms22168510
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Hypothalamic Oxytocin Pathway to Locus Coeruleus and Augmented Attention with Chemogenetic Activation of Hypothalamic Oxytocin Neurons

Abstract: The tightly localized noradrenergic neurons (NA) in the locus coeruleus (LC) are well recognized as essential for focused arousal and novelty-oriented responses, while many children with autism spectrum disorder (ASD) exhibit diminished attention, engagement and orienting to exogenous stimuli. This has led to the hypothesis that atypical LC activity may be involved in ASD. Oxytocin (OXT) neurons and receptors are known to play an important role in social behavior, pair bonding and cognitive processes and are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Indeed, OT receptors are expressed in the LC and DR 30 . Using optogenetic technique, it has been shown that OT is released into the LC from hypothalamic PVN OT fibers, activating noradrenergic neurons by co-release of OT and glutamate 31 . Noradrenergic neurons in the LC and serotonergic neurons in the DR are important transitional nuclei for the descending pain inhibitory system 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, OT receptors are expressed in the LC and DR 30 . Using optogenetic technique, it has been shown that OT is released into the LC from hypothalamic PVN OT fibers, activating noradrenergic neurons by co-release of OT and glutamate 31 . Noradrenergic neurons in the LC and serotonergic neurons in the DR are important transitional nuclei for the descending pain inhibitory system 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Disturbing OT neuronal activity in the SON can activate the amygdala in rats ( Liu et al, 2017 ), a brain region facilitating social anxiety and fear in humans ( Meixner et al, 2019 ). Optogenetic excitation of PVN OT fibers excites noradrenergic neurons in the locus coeruleus and augments attention to novel objects by co-release of OT and glutamate in male rats ( Wang et al, 2021b ). Fear-related behaviors are rigidly controlled by the medial prefrontal cortex (mPFC) while OT-mediated decrease in neuronal activity in the mPFC could facilitate social buffering in rats ( Jung et al, 2021 ).…”
Section: Higher Brain Functionsmentioning
confidence: 99%
“…(1) (Cuneo et al, 2021;Jahangard et al, 2020;Meixner et al, 2019); (2) (Jung et al, 2021;Liu et al, 2021a;Maier et al, 2019;Wang et al, 2021b); (3) (Runyan et al, 2021;Sabe et al, 2021; (4) (John & Jaeggi, 2021;Shishido et al, 2021;Yoshihara et al, 2018;Yuan et al, 2019); (5) (Reichova et al, 2021;Tyzio et al, 2014); (6) (Francesconi et al, 2021;Huang et al, 2021;Jimenez et al, 2015;Li et al, 2020; (7) (Feifel et al, 2012;Guastella et al, 2008;Latt et al, 2018;Plasencia et al, 2019;Tse et al, 2018); (8) (Bertoni et al, 2021;Hu et al, 2015;Larrazolo-Lopez et al, 2008); (9) (Kreutzmann & Fendt, 2021;Takahashi et al, 2020 (10) (Fisher et al, 2021;La Fratta et al, 2021;Torres et al, 2022;Warrener et al, 2021); (11) (Borroto-Escuela et al, 2021;Matsushita et al, 2019;Xie et al, 2022;Yoshida et al, 2009); (12) …”
Section: Pro-social Behaviormentioning
confidence: 99%
“…Oxt is known to increase LC adrenergic receptor responsiveness and thus enhance salience of received cues in rats ( Petersson et al, 1998 ). Optogenetic activation of PVH-Oxt neurons in rat brain resulted in downstream activation of LC-noradrenaline followed by an enhanced attention to novel objects suggesting that Oxt directly regulates attention by modulating LC responses ( Wang et al, 2021 ). The LC also receives monosynaptic inputs from another attention relevant area called the pedunculopontine nucleus (PPN), an area with abundant Oxt neuronal fibers.…”
Section: Oxytocin Associated Circuitry In Internal State Controlmentioning
confidence: 99%